4a-3a+2b-8b=

Simple and best practice solution for 4a-3a+2b-8b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a-3a+2b-8b= equation:


Simplifying
4a + -3a + 2b + -8b = 0

Combine like terms: 4a + -3a = 1a
1a + 2b + -8b = 0

Combine like terms: 2b + -8b = -6b
1a + -6b = 0

Solving
1a + -6b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '6b' to each side of the equation.
1a + -6b + 6b = 0 + 6b

Combine like terms: -6b + 6b = 0
1a + 0 = 0 + 6b
1a = 0 + 6b
Remove the zero:
1a = 6b

Divide each side by '1'.
a = 6b

Simplifying
a = 6b

See similar equations:

| 14y+12=18 | | 14y+8=12 | | 2.5x+2=-3 | | x^2-32x+54=0 | | 2/7m(4m-18)=12 | | 5(n-3)=35 | | ((1/3)x)-4=(12/7)-((5/6)x) | | 2x(2)+2y(2)=32 | | 2p*3+6= | | 2+-6k+13k*13k+92k*92k*92k= | | 9x-6y=16 | | 3995=ln(0.25x) | | 8d-1=21 | | 3k*3k-8k+6k*6k*6k+2k-5k*5k*5k+k*k*k+2k*2k+5-3= | | 1x+6+9+15=29 | | 9(m+1)=24 | | (H-6)+20=-4 | | y^2-20y=90 | | 25-d+2d-14= | | 3x+5=61 | | 4(3b-1)+6=5(b+4) | | 15a*15a+ab-6b*6b-2a*2a-5ab-2a*2a+4ab+b*b= | | 80=4(2x-3)+20 | | x(2x+1)=19 | | 6n-4=3n+8 | | 8x+11-3x=46 | | x-4/4-1=x-12/5 | | 1/2x-5=5/8x | | 4(5x+10)-16x+8=40 | | a+12-3a+4a-30= | | p*p-p*p*p*p-p*p*p+2p*2p*2p+4p*4p*4p*4p-3p*3p+3p*3p= | | x^2+0.03x-0.91=0 |

Equations solver categories